Rediscovering the hidden gateway to the seafood capital of the Philippines (a passenger and cargo port terminal infrastructure) - Abella, Evelyn D.
Roxas City is blessed with a scenic view of an ocean splendidly shimmering as the day rises and sets forth. Its glittering waters enhance the relaxing ambiance that one experiences as one traverse the sea. With the gentle breeze smoothly flowing and the light sound charmingly whistling…nothing could be bartered as to experience nature in its magical means. This enchanting nature’s beauty unlicks the hidden gateway to the Seafood Capital of the Philippines. The gateways that will not only open windows for a progressive maritime industry but will also lead the doors to the City’s tourism industry. Culasi port has been the center of trading even before Spaniards conquistador came. Its accessibility to the sea made such facility convenient to process sea-side businesses and transactions and that primarily includes shipping services. As the entry point to the heart of the province, it opens ample opportunities to let economic productivity boom within the City and thus it is significant that redesigning such facility is dearly necessary to cater future cargo and passenger movements. As the country aims to be a maritime hub of the Asia Pacific region, the city, is at the same time aiming to be integrated in the international trading system by locally implementing these international design standards to such facility. The essence of a true Capizeño speaks out for the City’s unique character that basically is important in creating an architectural identity for the Province. This uniqueness is vital in distinguishing one’s architectural heritage from all other provinces that travelers seek to discover. A worthwhile experience attracts more tourists coming to and fro; leaving a lasting impression.